RP-HPLC Analysis of 6-Gingerol and Assessment of Antioxidant Activities in EMS Treated Ginger - Sandeep Pai, Firdose Kolar; Ghansham Dixit, Nilesh Pawar, Mansingraj Nimbalkar (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Present investigation deals with RP-HPLC analysis of 6- gingerol from rhizome of ginger treated with EMS at different concentrations. The concentration levels were 0.10, 0.15, 0.20 and 0.25% for EMS 8 hour treatment and 0.30, 0.40, 0.50 and 0.60% for 4 hour treatment. The antioxidant activity of extracts were assessed by DPPH radical scavenging method and FRAP. Total phenolic content was determined using the FolinÃ¢â‚¬â€œCiocalteu (FÃ¢â‚¬â€œ C) method. The results showed that the 6- gingerol content increased with an increase in EMS dose initially (0.30%) and decreased at the higher dose (0.60%) in EMS 4 hrs treatments while there was no definite trend observed in EMS 8 hrs treatments. Antioxidant activity and the total phenolic content showed significant correlation with 6-gingerol content.